Darkness on the edge of town: mapping ‘Asian’ London in popular culture (2013)
Th is chapter traces South Asian diaspora in post-colonial suburbia through popular culture. It focuses on this demographically young population, so eff ectively is about UK-based South Asian youth culture. Th e ‘town’ it takes for consideration is arguably not just a town but the super-diverse megacity of London, the United Kingdom’s capital. Th e word ‘Asian’ itself is fraught with complexity. In UK parlance, it normally means populations with origins in the subcontinent or ex-British India. Yet it connotes a plurality of communities. Describing west London and its overspill alone, Malkani ( 2006 :12) through the character Jas explains in slang style that ‘the Sikh boys . . . ran Southall . . . the Muslim boys ran Slough. Hounslow’s more a mix of Sikhs, Muslims an Hindus, so the brown-on-browns tended to be just one-on-ones stead a thirty desis fi ghting side by side’. Th e comment appears to be alluding to a divide and rule principle that had meant less unity within the old Asian-bloc category. Within these faith groups are Pakistanis, Bangladeshis and Indians to name but three. Th e word ‘desi’ is oft en taken by these groups to refer to ‘of the homeland’ e.g. a second generation Asian might express a longing to return to their parents home ‘to eat some desi (home-cooked) food’.